Flavonoids from Verbascum thapsus Protect Against Nephrotoxicity in Rats: Flavonoid dari Verbascum thapsus Melindungi Terhadap Nefrotoksisitas pada Tikus - Bukhibkh , Hawraa Chasib (Academia Open, 2024)
General Background: Nephrotoxicity induced by carbon tetrachloride (CCl4) poses significant health risks, prompting the exploration of natural antioxidants for renal protection. Specific Background: Verbascum thapsus, a plant known for its flavonoid content, has shown potential in mitigating oxidative stress, but its specific protective effects against CCl4-induced nephrotoxicity remain under-investigated. Knowledge Gap: While previous studies have indicated antioxidant properties of flavonoids, their efficacy in renal preservation in vivo has not been fully elucidated. Aims: The study evaluated the antioxidative and nephroprotective properties of flavonoids from Verbascum thapsus leaves in a rat model of CCl4-induced nephrotoxicity.Results: Rats were divided into three groups: control, CCl4-treated, and flavonoid plus CCl4-treated. Biochemical analyses revealed that CCl4 significantly elevated malondialdehyde (MDA), urea, creatinine, and uric acid levels while decreasing superoxide dismutase (SOD) and glutathione (GSH) levels. Notably, flavonoid administration markedly reduced MDA, urea, creatinine, and uric acid levels and enhanced SOD and GSH levels compared to the CCl4-only group. Novelty: This study uniquely highlights the protective role of flavonoids from Verbascum thapsus against nephrotoxicity, demonstrating both their antioxidative capacity and renal preservation in an experimental model. Implications: The findings support the potential use of Verbascum thapsus as a therapeutic agent in the management of kidney diseases, suggesting further investigation into its application in clinical settings to address nephrotoxicity and related renal disorders. Highlights: Nephroprotective: Flavonoids significantly protect against CCl4-induced kidney damage. Biochemical Enhancement: Improved antioxidant levels; reduced harmful biochemical indicators. Therapeutic Potential: Supports natural treatments for kidney diseases. Keywords: Verbascum thapsus, flavonoids, nephrotoxicity, antioxidants, carbon tetrachloride